GAMBARAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR PADA KARYAWAN TETAP PT. “JCT” STEEL MILLS - Dorcas Ayu Lestari; Devi Jatmika (Psibernetika, 2014)
Globalization has created great changes towards industrial companies in Indonesia. As the result, competition among industrial companies become very tough. Manufacture industries is still a leading sector for economic growth. ”JCT” Steel Mills company is one of large steel mills industrial company that established since 1992. This research is going to describe Organization Citizenship Behavior (OCB) of employees in ”JCT” Steel Mills company. OCB is known as one‟s willing behaviors to support organization effectiveness. This research is quantitative descriptive research. OCB questionnaire is distributed to 95 employees. Data has been analysed with T-scale. The general result reveals all employees is in moderate level of OCB. The dimension of OCB which are: civic virtue and consciousness is 74.7%, helping behavior is 71.6%, sportmanship is 68.4% , courtesy is 69.5%. Some factors like communication problem among senior and junior level and other divisions are indicated as barriers of courtesy and sportmanship. Keywords: Organizational Citizenship Behavior, Employees, Organization